Oxidation in EPA‐ and DHA‐rich oils: an overview. Issue 3 (24th March 2016) - Ismail, Adam; Bannenberg, Gerard; Rice, Harry B.; Schutt, Ellen; MacKay, Douglas
Abstract : Oxidation of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) rich omega‐3 oils (hereafter referred to as either EPA and DHA or omega‐3) is a complicated topic, but an important one to understand. A significant number of consumers cite fishy burp and/or taste, thought to be the result of oxidation, as one of the main reasons they do not consume EPA and DHA rich oils. In addition, consumers note that some articles have raised concerns about the potential for adverse effects associated with consumption of oxidized oils. Measuring oxidation in omega‐3 oils is complicated due to the differences in chemical and physical characteristics of many commercially available products, which means not all methods to determine quality are appropriate for all types of oils. A number of consumer advocacy groups, product quality seal programs and academic groups have published data on levels of oxidation in omega‐3 oils. Overall, this data shows that commercially available omega‐3 supplements are low in oxidation. If consumers have a poor sensory experience with their omega‐3 product, they should try another product as an alternative.